Plasmodium falciparum serology: A comparison of two protein production methods for analysis of antibody responses by protein microarray. - Tate Oulton; Joshua Obiero; Isabel Rodriguez; Isaac Ssewanyana; Rebecca A Dabbs; Christine M Bachman; Bryan Greenhouse; Chris Drakeley; Phil L Felgner; Will Stone; Kevin K A Tetteh (PLoS ONE)
The evaluation of protein antigens as putative serologic biomarkers of infection has increasingly shifted to high-throughput, multiplex approaches such as the protein microarray. In vitro transcription/translation (IVTT) systems-a similarly high-throughput protein expression method-are already widely utilised in the production of protein microarrays, though purified recombinant proteins derived from more traditional whole cell based expression systems also play an important role in biomarker characterisation. Here we have performed a side-by-side comparison of antigen-matched protein targets from an IVTT and purified recombinant system, on the same protein microarray. The magnitude and range of antibody responses to purified recombinants was found to be greater than that of IVTT proteins, and responses between targets from different expression systems did not clearly correlate. However, responses between amino acid sequence-matched targets from each expression system were more closely correlated. Despite the lack of a clear correlation between antigen-matched targets produced in each expression system, our data indicate that protein microarrays produced using either method can be used confidently, in a context dependent manner, though care should be taken when comparing data derived from contrasting approaches.